PERFORMANCE ANALYSYS OF ORGANIZATIONAL EFFECTIVENESS IN THE GOVERNMENT BANDAR LAMPUNG CITY - Epi Parela (Saburai International Journal of Social Sciences and Development, 2021)
This study aims to determine the effect of organizational culture and work motivation on employee performance at the Department of Industry and Trade of Pesawaran Regency. The type of research used in this study is an explanatory research model. This study used 27 research respondents. There are three variables in this study, namely: 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable where organizational culture (X1) and work motivation (X2) are independent variables and employee performance (Y) is the dependent variable. . Based on data analysis, it has been found that the answers to the hypothesis are as follows; There is an influence of organizational culture (X1) on employee performance (Y), with a level of influence of 46.2%. There is an effect of work motivation (X2) on employee performance (Y) with an influence level of 13.6%. There is an influence of organizational culture (X1) and work motivation (X2) together on employee performance (Y) with an influence level of 55.4%.